INOVASI PERTANIAN MODERN RAMAH LINGKUNGAN UNTUK MENDUKUNG KETAHANAN PANGAN LOKAL DI BIJAI GREEN HIDROPONIK - Sipayung, Mei Linda; Yanti , Mariana Eva (Jurnal Inovasi Pengabdian Masyarakat, 2025)
Hydroponics is a method of cultivating plants without using soil, but rather with mineral nutrient solutions tailored to the plant's needs. Binjai Green Hydroponics is one form of modern agricultural implementation that utilizes a hydroponic system as a solution to increase agricultural productivity amidst limited land in the urban periphery and high food demand. This study aims to examine the concept, advantages, and application of the Binjai Green Hydroponic system in supporting local food security. The research method was conducted using a qualitative descriptive approach through literature studies, field observations, and interviews with hydroponic practitioners in the Binjai area. The results show that the hydroponic system can increase water use efficiency by up to 80%, accelerate the vegetable harvest period, and produce more hygienic and high-quality products. The implementation of Binjai Green Hydroponics also has the potential to encourage community economic growth through urban farming-based agribusiness.